Literatur Review: Perbedaan Menghafal Al-Qur’an Dengan Metode Takrir, Talaqqi dan Odoa Terhadap Perkembangan Hafalan Anak-Anak Usia Sekolah Dasar - Salman Salman; Safrizal Safrizal (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2021)
Memorizing the Qur'an with various methods applied is something extraordinary for every child to be able to do. Especially in memorization, a method is needed so that elementary age children are not bored and bored in studying it. So the right and good method in this article offers a very good method, namely the panipati method.